Pengaruh Dinamika Makroekonomi Terhadap Non-Performing Financing Perbankan Syariah di Indonesia: Pendekatan Non-Linear Autoregressive Distributed Lag (NARDL) Periode 2015-2025 - Fahriza Diani Jati; Herlitah Herlitah; Siti Fatimah Zahra (Indo Publishing, 2026)
This study aims to investigate the dynamic and asymmetric responses of Islamic banking financing risk (Non-Performing Financing/NPF) in Indonesia to macroeconomic variable shocks, specifically Economic Growth (IPI), Inflation, and Exchange Rate. This research is motivated by the urgency of risk mitigation amidst the post-pandemic